Anatomical Suitability of the Aortic Arch Arteries for a 3-Inner-Branch Arch Endograft. (February 2021) - Spanos, Konstantinos; Haulon, Stephan; Eleshra, Ahmed; Rohlffs, Fiona; Tsilimparis, Nikolaos; Panuccio, Giuseppe; Kölbel, Tilo
Purpose: To analyze aortic arch anatomy of patients who were already treated with a 2-inner-branch arch endograft (2-IBAE) in order to assess the anatomical suitability of the supra-aortic arteries as target vessels for a 3-IBAE. Materials and Methods: Three different configurations of the Cook Zenith Arch endograft were designed with distances of 110 mm (model 1), 90 mm (model 2), and 70 mm (model 3) between the orifices of the first and third inner branches. Preoperative measurements of the aortic arch anatomy from 104 consecutive patients treated electively with custom-made 2-IBAEs at 2 European centers between 2014 and 2019 were analyzed. A previously described standard methodology with a planning sheet was used. Data and measurements included the treatment indication for the aortic arch pathology, the type of landing zone, the type of arch, and the inner and outer lengths of the ascending aorta from the sinotubular junction to the innominate artery (IA). Additionally, the diameters and clock positions of the IA, left common carotid artery (LCCA), and left subclavian artery (LSA) were assessed, along with the distances between the IA and the LCCA, the IA and the LSA, and the distal landing zone. Results: Type I was the most common arch configuration (75/104, 72%). The mean clock positions were 12:30±00:28 for the IA, 12:00±00:23 for the LCCA, and 12:15±00:29 for the LSA. The mean diameters were 14.2±2.2 mm for the IA, 8.8±1.8 mm for the LCCA, and 10.5±2 mm for the LSA. The mean distances between the IA and LCCA and between the IA and LSA were 14.7±5.8 mm and 33±9.4 mm, respectively. Model 2 (branch distance 90 mm) had the highest suitability (79%), while models 1 and 3 showed suitability rates of 73% and 68%, respectively. The most frequent exclusion criterion in all models was the diameter of the LSA, followed by the IA to LSA distance. Conclusion: The suitability for a 3-IBAE among patients who had a 2-IBAE implanted is high, favoring a 90-mm distance between the retrograde LSA branch and baseline.